Risk of hypospadias in relation to maternal occupational exposure to potential endocrine disrupting chemicals. Issue 8 (25th July 2003) - Vrijheid, M; Armstrong, B; Dolk, H; van Tongeren, M; Botting, B
Abstract : Background: Reported rises in the prevalence of hypospadias and other abnormalities of the male reproductive system may be a result of exposure to endocrine disrupting chemicals. Aims: To analyse the relation between risk of hypospadias and maternal occupation, particularly with regard to exposure to potential endocrine disrupting chemicals (EDCs). Methods: Data (1980–96) from the National Congenital Anomaly System (NCAS) were used to analyse the proportion of all congenital anomaly cases (n = 35 962) which were notified with hypospadias (n = 3471) by occupational codes (348 individual job titles) and by categories of exposure to potential EDCs from a job exposure matrix. Results: Five individual occupations (of 348) showed nominally statistically significant excesses, none of which had possible or probable exposure to potential EDCs. Odds ratios for "possible" or "probable" compared to "unlikely" exposure to potential EDCs did not show statistically significant increases in any of the EDC categories after adjustment for social class of the mother and father, nor was there evidence of an upward trend in risk with likelihood of exposure. In the 1992–96 time period odds ratios were increased for hairdressers (the largest group exposed to potential EDCs) and for probable exposure to phthalates (of which hairdressers form the largest group) before social class adjustment. Conclusions: There was little evidence for a relation between risk of hypospadias and maternal occupation or occupational exposure to potential EDCs, but as the exposure classification was necessarily crude, these findings should be interpreted with caution.